Combination cancer treatment through photothermally controlled release of selenous acid from gold nanocages. (September 2018) - Cheng, Haoyan; Huo, Da; Zhu, Chunlei; Shen, Song; Wang, Wenxia; Li, Haoxuan; Zhu, Zhihong; Xia, Younan
Abstract: Selenite, one of the inorganic forms of selenium, is emerging as an attractive chemotherapeutic agent owing to its selectivity in eradicating cancer cells. Here we demonstrate a new formulation of nanomedicine based on selenous acid, which is mixed with lauric acid (a phase-change material with a melting point around 43 °C) and then loaded into the cavities of Au nanocages. The Au nanocages can serve as a carrier during cell endocytosis and then as a photothermal agent to melt the lauric acid upon the irradiation with a near-infrared laser, triggering the swift release of selenous acid. The photothermal and chemo therapies can also work synergistically, leading to enhanced destruction of cancer cells relative to normal cells. Our systematic study suggests that the impaired mitochondrial function arising from the ROS generated through combination treatment is responsible for the cell death. This study offers an appealing candidate that holds great promise for synergistic cancer treatment. Graphical abstract: Striving together for higher efficacy : The cavities inside Au nanocages can be loaded with a mixture of an anticancer drug and a phase-change material to achieve a synergetic effect in killing cancer cells more efficiently through a combination of photothermal and chemo therapies.